Protective effect of zinc against A2E-induced toxicity in ARPE-19 cells: Possible involvement of lysosomal acidification - Jeong A. Choi; Bo-Ra Seo; Jae-Young Koh; Young Hee Yoon (Heliyon)
A key pathogenic mechanism of dry age-related macular degeneration (AMD) is lysosomal dysfunction in retinal pigment epithelium (RPE) cells, which results in the accumulation of lipofuscins such as A2E (N-retinylidene-N-retinylethanolamine) that further compromises lysosomal function. This vicious cycle leads to cell death and poor visual acuity. Here, we established an in vitro model of AMD by treating a human RPE cell line (ARPE-19) with A2E and examined whether raising zinc levels confers protective effects against lysosomal dysfunction and cytotoxicity. MTT assay showed that A2E induced apoptosis in ARPE-19 cells. pHrodo™ Red fluorescence staining showed that lysosomal pH increased in A2E-treated ARPE-19 cells. Treatment with a zinc ionophore (clioquinol) reduced A2E accumulation, restored lysosomal pH to the acidic range, and reduced A2E-induced cell death, all of which were reversed by the addition of a zinc chelator (TPEN). Consistent with the in vitro results, subretinal injections of A2E in mouse eyes resulted in the death of RPE cells as well as lysosomal dysfunction, all of which were reversed by co-treatment with clioquinol. Our results suggest that restoring the levels of intracellular zinc, especially in lysosomes, would be helpful in mitigating A2E-induced cytotoxic changes including lysosomal dysfunction in RPE cells in the pathogenesis of AMD.